Balanço de Radiação em Superfície na Região Metropolitana do rio de janeiro - Mesquita, Francisco L. L.; Marques Filho, Edson P.; Karam, Hugo A.; França, José R. A.; Oliveira, Amauri P.; Codato, Georgia (Ciência e Natura, 2011)
.